(untitled) (SAARC Journal of Agriculture, 2018)
An experiment to investigate the effect of seed rate (5, 7.5, 10, 12.5 and 15 kg ha-1) and row spacing (30, 45 and 60cm) on agronomic characteristics of plants including stem densitym-2, plant height, stem diameter, number of heads m-2, number of heads per plant, number of grains per head, 1000-grain weight and grain yield was conducted using the cultivar “Sorghum 2011” for two years 2016 and 2017. Seed rates and row spacing had significant effect on plant height, plant density m-2, number of heads m-2, number of grains per head and grain yield. Row spacing had non-significant effect on stem diameter, number of heads per plant and 1000-grain weight. Row spacing at 30 cm produced the highest number of plants m-2 and plant height. Plant height increased with increase in seed rate in all the row spacing. Stem diameter decreased with increase in the seed rate and row spacing. Narrow row spacing (30 cm) and low seeding rate (5 kg ha-1) produced the maximum grain yield consistently during both years. Lower yields were recorded in the treatments having greater row spacing (60 cm) and higher seed rates (7.5, 10, 12.5 & 15 kg ha-1). Higher seed rates and wider row spacing induced morphological changes rendering plants to lodging. SAARC J. Agri., 15(2): 81-91 (2017)